Homogenizing Deconcentration: Estimation and Simulation - Scott, John T. (The Review of Economics and Statistics, 1980)
Asch, Peter, and Joseph J. Seneca, Is Collusion Profitable? this REVIEW 58 (Feb. 1976), 1-12. Block, M. K., F. C. Nold and J. G. Sidak, The Deterrent Effect of Antitrust Enforcement: A Theoretical and Empirical Analysis, Technical Report ISDDE-1-78, Hoover Institution, Dec. 1978. Clabault, James M., and John F. Burton, Jr., Sherman Act Indictments, 1955-1965 (New York: Federal Legal Publications, 1966). Feinberg, Robert M., Structure and Employment Instability, this REVIEW 61 (Nov. 1979), 497-505. , The Lerner Index, Concentration, and the Measurement of Market Power, Southern Economic Journal 46 (Apr. 1980), 1180-1186. Guth, Louis A., Robert A. Schwartz, and David K. Whitcomb, The Use of Buyer Concentration Ratios in Tests of Oligopoly Models, this REVIEW 58 (Nov. 1976), 488-492. Hay, George A., and Daniel Kelley, An Empirical Survey of Price-Fixing Conspiracies, Journal of Law and Economics 17 (Apr. 1974), 13-38. Lustgarten, Steven H., The Impact of Buyer Concentration in Manufacturing Industries, this REVIEW 57 (May 1975), 125-132. , The Use of Buyer Concentration Ratios in Tests of Oligopoly Models: Reply, this REVIEW 58 (Nov. 1976), 492-494. Omstein, Stanley I., Industrial Concentration and Advertising Intensity (Washington, D.C.: American Enterprise Institute, 1977). Palmer, John, The Profit-Performance Effects of the Separation of Ownership from Control in Large U.S. Industrial Corporations, Bell Journal of Economics 4 (Spring 1973), 299-302. Trade Regulation Reporter, Vol. 4, New U.S. Antitrust Cases (Chicago: Commerce Clearing House, 1979).